OCCUPATIONAL HEALTH AND SAFETY PRACTICES_ A CASE STUDY OF A CHEMICAL INDUSTRY (Journal of Medical & Health Sciences Review, 2025)
Background and Objective: The research critically examines XYZ chemical industry's OHS management, emphasizing EHRA challenges and non-compliance factors. Objectives include evaluating health and safety systems, identifying/mitigating risk factors, and suggesting measures. The aim is to assess working conditions, ensure compliance, and recommend steps for eliminating health hazards.Methodology: The methods used to carry out the study at XYZ chemical industry, Lahore are: 1) Interview/questionnaires, 2) Meetings, 3) Gap analysis, 4) Desk study, 5) Self-observation / walk through surveys, 6) Hazard identification / risk assessment.Result: Conclusion: Area in-charges provided input on identified risks' severity and probability, followed by assigning ratings. High-risk areas (Production, Storage, Maintenance, Drum House, Quality Assurance labs) with ratings beyond 6 are deemed unacceptable, prompting proposed control actions for severity reduction